Pengaruh Gaji dan Insentif terhadap Kinerja Karyawan PT. Tenma Indonesia Karawang Factory - Akhmad Subhan Riyadi; Suroso Suroso; Maman Mulya Karnama (Journal of Management and Bussines (JOMB), 2024)
This research aims to evaluate how salaries and incentives influence employee performance improvement at PT. Tenma Indonesia Karawang Factory. Research data was collected through questionnaires and then analyzed using SPSS version 26 software with a multiple linear regression approach. The research results show that the calculated t result of the salary variable is 6.775 > t table 1.984, meaning that the salary variable has a partially significant effect on the performance variable, while the t calculated incentive variable is 1.216 < t table 1.984, meaning that the incentive variable has no partial significant effect on the performance variable. And it is known that the calculated F value of the salary and incentive variables is 53.257 > F table 3.090, meaning that it has a significant simultaneous effect on the performance variable. In conclusion, companies must be able to provide appropriate salaries to their employees in order to advance the company and encourage employee performance because there is a relationship between salary variables and performance variables. The low incentives received by employees mean that employee performance cannot be measured by the number of incentives received. Companies must be able to provide appropriate incentives for their employees. Keywords : Salary, Incentives, Employee performance